1978
DOI: 10.1071/ar9780327
|View full text |Cite
|
Sign up to set email alerts
|

Selection for reproduction rate in Australian Merino sheep: direct responses

Abstract: Two groups of Australian Merinos have been under selection for low (O) and high (T) reproduction rate since 1954, and a third (B) for high rate since 1959. The O and T groups were founded on Peppin ewes from one flock which had borne singles (or twins) in two successive years, mated to single- (or twin-) born rams from the same flock. The B group was founded on two quintuplet rams and ewes born in multiple births (13 in one intake, 91 in a second), from a medium-wool non-Peppin flock belonging to the Seears Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1
2

Year Published

1980
1980
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 0 publications
0
14
1
2
Order By: Relevance
“…El promedio de 1,71 en PRO en el presente trabajo se atribuye principalmente al proceso de selección que se lleva a cabo en este rancho al utilizar ovejas nacidas de partos múltiples, aunado al buen manejo general del rebaño, especialmente en el aspecto de alimentación. Este procedimiento de selección fue utilizado con bastante éxito en Nueva Zelanda (Clarke 1972) y Australia (Turner 1978), logrando incrementar con bastante éxito la prolificidad en ovinos Romney Marsh y Merino, respectivamente.…”
Section: Promedios Generales De Factores Ambientalesunclassified
“…El promedio de 1,71 en PRO en el presente trabajo se atribuye principalmente al proceso de selección que se lleva a cabo en este rancho al utilizar ovejas nacidas de partos múltiples, aunado al buen manejo general del rebaño, especialmente en el aspecto de alimentación. Este procedimiento de selección fue utilizado con bastante éxito en Nueva Zelanda (Clarke 1972) y Australia (Turner 1978), logrando incrementar con bastante éxito la prolificidad en ovinos Romney Marsh y Merino, respectivamente.…”
Section: Promedios Generales De Factores Ambientalesunclassified
“…The prolificacy of the Booroola Merino is well established (Turner, 1978) and individual ewes can have up to 11 ovulations . It has been proposed that a major gene is responsible for the extremes in ovulation rate within the Booroola flock and three putative genotypes, FF (homozygous carriers of the fecundity gene), F+ (heterozygous carriers) and + + (non-carriers) have been proposed, based on maximum ovulation rates of > 5, < 5 and > 3 and < 3 respectively, assessed from repeated observations (Davis, Montgomery, Allison, Kelly & Bray, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…These flocks include lines from a Peppin flock selected for (T) and against (0) multiple births and a high-fecundity, medium-wool, non-Peppin flock, the Booroola (B). Their genetic history and flock performances have been described by Turner (1978). Trounson et al (1974) reported that lambs from the 0 flock had more ovarian primordial follicles than lambs from the T flock and concluded that genetic selection for the incidence of multiple births has resulted in changes in the number of primordial follicles of the post-natal lamb.…”
Section: Introductionmentioning
confidence: 99%